Evaluation of the role of susceptibility-weighted imaging in thrombolytic therapy for acute ischemic stroke. (June 2017) - Zhao, Guangjian; Sun, Ling; Wang, Ziran; Wang, Liquan; Cheng, Zhongrong; Lei, Hongyan; Yang, Daiqun; Cui, Yansen; Zhang, Shirui
Highlights: Acute ischemic stroke (AIS) is a common cerebrovascular condition that has a high incidence. This study only performed qualitative analysis of low-intensity signal changes in SWI. Multi-modality susceptibility-weighted imaging used individualized thrombolytic therapies. Abstract: We inspected low-intensity venous signals and microbleeds in patients with acute ischemic stroke (AIS) using susceptibility-weighted imaging (SWI) before and after administration of within-thrombolytic-time-window thrombolytic therapies, and observed their prognosis and safety, in order to guide individualized thrombolytic therapies. Patients with AIS were divided into groups A or B according to the presence of symmetric or asymmetric veins on SWI, and were re-inspected by SWI after intravenous thrombolysis using recombinant tissue plasminogen activator (rt-PA). The National Institutes of Health stroke scale (NIHSS) score before treatment and at 1-h and 24-h posttreatment in the two groups were 11.9, 7.3, and 7.1 in group A, 12.4, 8.2, and 7.9 in group B, significant difference was detected between the two groups after treatment. The 90-day mortality rate was 0, and the incidences of cerebral microbleeds (CMBs) and symptomatic cerebral hemorrhage (SCH) were 17.6%, and 0% in group A, 25.6% and 0% in group B, respectively. The incidences of CMBs and SCH in group A were lower than those in group B, but the intergroup differences were not statistically significant ( P  > 0.05). The 90-day neurological improvement rates in the two groups were 70.2% and 58.1%, respectively, and group A showed a significantly better prognosis than group B ( P  < 0.05). Thus, low-intensity venous signals in SWI can be used to evaluate a low level of perfusion, post-thrombolytic prognosis, and bleeding indexes, and can therefore be used to guide individualized thrombolytic therapies.